Past, Present, and Future of the Pathophysiological Model of the Basal Ganglia - Obeso, Jose A.; Lanciego, Jose L. (Frontiers in Neuroanatomy, 2011)
The current model of basal ganglia was introduced two decades ago and has settled most of our current understanding of basal ganglia function and dysfunction. Extensive research efforts have been carried out in recent years leading to further refinement and understanding of the normal and diseased basal ganglia. Several questions, however, are yet to be resolved. This short review provides a synopsis of the evolution of thought regarding the pathophysiological model of the BG and summarizes the main recent findings and additions to this field of research. We have also tried to identify major challenges that need to be addressed and resolved in the near future. Detailed accounts and state-of-the-art developments concerning research on the basal ganglia are provided in the articles that make up this Special Issue.